Agro - Socioeconomic Newsletter : Indonesian Center for Agricultural Socio Economic and Policy Studies (ICASEPS) Vol.11 No.1, April 2018 - Redaksi (ICASEPS, 2018)
- Strengthening Smallholders' Institution toward Commercial Farmers - Indonesia Agriculture Sector Outlook 2018 - Regulation of ministry of Trade (Permendag) No.21/2018 on Maize Import Stipulation - ...